The effect of sodium hydroxide on drag reduction using banana peel as a drag reduction agent - Kaur, H. (American Institute of Physics Inc., 2018)
Drag reduction is observed as reduced frictional pressure losses under turbulent flow conditions. Drag reduction agent such as polymers can be introduced to increase the flowrate of water flowing and reduce the water accumulation in the system. Currently used polymers are synthetic polymers, which will harm our environment in excessive use of accumulation. A more environmentally-friendly drag reduction agent such as the polymer derived from natural sources or biopolymer, is then required for such purpose. As opposed to the synthetic polymers, the potential of biopolymers as drag reduction agents, especially those derived from a local plant source are not extensively explored. The drag reduction of a polymer produced from a local plant source within the turbulent regime was explored and assessed in this study using a rheometer, where a reduced a torque produced was perceived as a reduction of drag. This method proposed is less time consuming and is more practical which is producing carboxymethylcellulose from the banana peel. The cellulose powder was converted to carboxymethylcellulose (CMC) by etherification process. The carboxymethylation reaction during the synthesizing process was then optimized against the reaction temperature, reaction time and solubility. The biopolymers were then rheologically characterized, where the viscoelastic effects and the normal stresses produced by these biopolymers were utilized to further relate and explain the drag reduction phenomena. The research was structured to focus on producing the biopolymer and to assess the drag reduction ability of the biopolymer produced. The rheological behavior of the biopolymers was then analyzed based on the ability of reducing drag. The results are intended to expand the currently extremely limited experimental database. Based on the results, the biopolymer works as a good DRA. Â© 2018 Author(s).